APLIKASI PELACAKAN ALUMNI FAKULTAS ILMU KOMPUTER - Ricky Zulfiandry; Eka Purnama Sari (LPPM UNIVERSITAS BINA INSAN, 2026)
Alumni tracking is an important need for higher education institutions because graduate data can be used for curriculum evaluation, quality assurance, and accreditation support. At the Faculty of Computer Science, Universitas Dehasen Bengkulu, alumni tracking was still conducted manually using questionnaires, making the process time-consuming, less efficient, and not always able to reach the minimum number of respondents. This study aims to develop a web-based alumni tracking application to support alumni data entry, stakeholder data entry, institutional characteristic assessment, graduate quality assessment, and the management of comments and suggestions. The system was developed using the System Development Life Cycle (SDLC), including analysis, requirement approval, design, development, testing, and release stages. The application was implemented using PHP, MySQL, and Apache. The results show that the application can store alumni and stakeholder data in a database, display recapitulations, and print assessment reports. Black box testing involving 26 scenarios showed that all functions were valid. Therefore, the application can support alumni tracking in a faster, more structured, and better documented manner.